The Levels of Critique. Pierre Bourdieu and the Political Potential of Social Theory - Mariano Croce (Sociologica, 2019)
This article centres on Pierre Bourdieu’s conception of social critique and its political potential. It first examines important objections to his view of the way in which critique works, particularly from those scholars who claim that it implies an objectivist notion of people’s cognition and agency. It continues by clarifying that this objection rests on a misplaced understanding of Bourdieu’s idea of the levels at which critique takes place. It then explores his understanding of the semantic struggle that social critique requires and what it takes to change the dominant configuration of the social. The analysis finally claims that this conception of critique, although far from objectivism, still retains an intellectualist inclination.